Role of Muscle Strengthening Exercise on Osteoarthritis of the Knee Joint - Azad, Abul Kalam; Nabi, Golam; Shakoor, MA; Moyeenuzzaman, MD (Journal of Medicine, 2011)
A total of 106 patients of osteoarthritis of knee were selected for the study. Out of 106 patients 26.41% were male and 73.58% were female. The female and male ratio is 2.78: 1. Mean age was 49.68 ± 9.16 years and house wives were maximum in number 75 (70.8%). They were divided into two groups, 52 patients in group–A, were treated with NSAID plus Exercise and another 54 patients in group-B, were treated with NSAID only. In both group patients were treated for six weeks duration. The improvement was assessed with WOMAC scoring system. Student’s‘t’ test was to see the level of significance. In present study, the patients groups those who received NSAID plus Exercise, improved more significantly (p= 0.001) than those who received NSAID only. So it can be concluded that quadriceps muscle strengthening exercise is effective in the patients with OA knee. Keyword: Osteoarthritis, Knee, Exercise. DOI: http://dx.doi.org/10.3329/jom.v12i2.8418 JOM 2011; 12(2): 120-124